Competitiveness of Indonesia’s nutmeg in global market - Rochdiani Dini; Wardhana Dadan; Deliana Yosini; Suminartika Eti; Wiyono Sulistyodewi Nur; Suardi Tennisya Febriyanti (Open Agriculture)
Nutmeg has been one of the oldest domestically and globally traded spices. This study aims to explore its competitiveness in the global market and examine factors increasing this competitiveness to provide potential policy recommendations for Indonesia’s nutmeg export improvement. Based on the analysis of competitiveness indicators, Indonesia’s export-oriented nutmeg undergoes declining productivity, low export prices, and stagnant progress of export competitiveness compared to other producing and exporting countries. From the results of panel data estimations, human resource endowment is the most influencing factor in boosting export competitiveness of nutmeg. Consumer Price Index, Foreign Direct Investment and agricultural shares in total gross domestic product have a positive link with export competitiveness. Logistics performance for international trade is also a potential driver for competitiveness. These findings imply that policies towards high export competitiveness of the nutmeg should be tailored to improving the productivity of the product standardising global trade procedures, advancing the quality of economic outcomes, and strengthening logistics infrastructure and management.